Classification of Product Review Sentiment Using Naive Bayes and Support Vector Machine Algorithms - Simangunsong, Pandi Barita Nauli; Fika Sirait, Matias Julyus; Tuti Andriani (Cattleya Darmaya Fortuna, 2026)
This review synthesizes research on